Szkice z dialektologii języka czeskiego 3. Czeska dialektologia od połowy XX w. i jej aktualne zadania - Bogoczová, Irena (Komisja Slawistyczna PAN, Oddział w Poznaniu, IFS UAM, Wydawnictwo PRO, 2017)
The article entitled The Czech Dialectology Since the Half of 20th Century and Its Current Challenges is an overview of what the Czech dialectology has been dealing with since the Second World War up to the present. The author focuses on the major researchers and their work, on the basic tasks of dialectology and on the development of the Czech dialectological thinking in general. It marginally touches on a new political and social situation in postwar Czechoslovakia, which also brought changes to the linguistic map of this country. From the comprehensive works, the author draws attention mainly to The Outline of Czech Dialectology by Jaroslav Bělič and the collective work Czech Language Atlas (Part 1–6). The selection of sub-topics and literature to a certain extent reflects the needs and preferences of Polish bohemists.
Keywords: Czech language; dialectology; toponyms; toponyms; research projects